Protective Measures during Construction of Ground Structures over Existing Underground Structures - A. A. Dalidovskaya; V. G. Pastushkov (Наука и техника)
Today, there is an acute issue of ensuring the safe operation of buildings and structures located in the immediate vicinity of new construction. The process of performing works on the installation of load-bearing structures and their further operation can have a negative impact on already existing facilities. In this regard, the task of developing innovative methods and tools to ensure the safe operation of such structures as subway running tunnels is very urgent. To solve it, a reliable forecast of additional deformation and appointment of a complex of protective measures are required.  In addition, much attention should be paid to the numerical modeling of the system “surface structures – protective measures – underground structures”. As an example of assessing the impact of new construction, namely, the erection of surface structures over existing underground  ones, one  can  cite  the  construction  of  a transport  interchange  at  the  intersection  of  Nezavisimosty  Avenue with Filimonov Street. As protective measures, a protective screen on bored piles has been used here, which made it possible to minimize significantly dynamic and static effects on the lining of tunnels and other underground structures of the subway. Effectiveness of protection application is confirmed by the result of monitoring the stress-strain state of running tunnel structures at all stages of traffic  intersection construction. Protective measures and continuous monitoring of the stress-strain state in structures help to avoid accidents during construction and further operation.